The economics of subsidising agriculture : a study of British policy - McCrone, Gavin (Museum Street London : George Allen & Unwind Limited, 1962)
The National Farmers' Union and others connected with the industry frequently point to the very real achievements of British agriculture since the war; outsiders often complain at the burden of support involved. The purpose of the book is to consider the part it ought to play and whether the subsidies are applied in the most suitable way.
Includes bibliographical references and index.
hza 29/06/2018
Loans
Keywords: Agriculture and state; Great Britain